Ultrathin Spider Silk Films: Insights into Spider Silk Assembly on Surfaces - Borkner, Christian B.; Lentz, Sarah; Mueller, Martin; Fery, Andreas; Scheibel, Thomas (ACS Applied Polymer Materials, 2019)
β-Sheets in natural spider dragline silk proteins are typically formed by polyalanine (An) as well as alanine-glycine (AG) and GGA sequences flanking these An regions. The hydrophobic β-sheet-rich regions are embedded in a hydrophilic amorphous matrix, and this phenomenon can be reflected as microphase separation, similar to that of block copolymers. Microphase separation occurs not only in fibers but also in cast spider silk films. Micellar-like structures form within the bulk of the film, while substrate surface as well as the film/air interface trigger explicit secondary structure formation in these layers. So far, only limited information is available concerning the mechanism of film assembly and microphase separation of spider silk proteins on surfaces. In this work, self-assembly and folding of eADF4(C16) was analyzed on steady silicon surfaces, dependent on the spider silk layer number and thickness. Based on the results, a model for structural features of spider silk films is proposed, combining block copolymer microphase separation theory with folding properties of recombinant eADF4(C16).
CRIS-Team Scopus Importer:2022-04-14
Keywords: microphase separation; protein structure; self-assembly; spider silk; spin-coating